AN ANALYSIS OF THE STRUCTURAL DYNAMICS OF RECENT POLITICAL SECULARISM IN TURKEY AND HABERMAS' PROPOSED REMEDIES - Hadi, Muhsin Abdul (International Relations Study Program, The Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2024)
Within the intricate structure of global political landscapes, the nation of Turkey emerges as a captivating subject of study, particularly when examining its progressive secularism and the complex interplay of socio-political dynamics. This study aims to examine the fundamental structural factors that surround the implementation of Turkey's present political secularism, while also employing Habermas' proposed notion of a post-secular society as an approach to address and resolve these intricacies. This study utilizes a qualitative research methodology by doing literature studies and relying on secondary data for data collection. The findings of this study suggest that Habermas's notion of a post-secular society has the potential to develop a sociopolitical structure that is more democratic and inclusive in the setting of Turkey where it is being investigated.